The right to housing and the residential tenancy regulation: should more be done at a European level? - Afonso, Ana (2024)
With a view to «combat social exclusion and poverty», a «right to social and housing assistance» has been included in the Charter of Fundamental Rights of the European Union (Article 34, para. 3). In spite of its vagueness, a right to housing can presently be considered a European Union principle. Protection of tenancies is a facet of an effective right to housing and European Union citizens could benefit from a stable and balanced tenancy contract law regulation. However, tenancy contract law has been left out of European Union «agenda». Creating a set of «model rules» could, nonetheless, be most useful. The absence of legal authority of such texts shall not diminish its importance since they slowly settle a common juridical heritage and influence decisions within the Member States. The drafting of a «default contract » or a set of «model rules» is, notwithstanding, far from being a simple task. Adjusting protection of the tenant’s interests to a functioning market is a huge challenge, already at a national level. In fact, wherever average wages are considerably low and rent prices are very high, reconciling landlords and tenants interests seems far from reachable.